Ship nationality regulations - كريم, م.ي.تاران محمد (Sulaimani Journal for Humanities, 2026)
The research addresses the legal nature of ships under Iraqi legislation. A ship is defined as a floating establishment intended for maritime navigation, including all its necessary accessories. Legally, the ship's accessories are treated in the same manner as the ship itself regarding ownership, disposition, mortgage, and seizure. A ship is considered a movable asset of a special nature, which necessitates subjecting it to a specific legal framework that includes the registration of all legal transactions involving it, such as sale, mortgage, and transfer of ownership, while allowing the security mortgage as an exception. A ship possesses a special civil status, including its name, home port, cargo capacity, and class. National ownership is considered a fundamental condition for acquiring Iraqi nationality for a ship, as nationality is granted when the ship is owned by Iraqis and flies the Iraqi flag. Acquiring nationality entails important legal effects, including distinguishing the ship from foreign vessels, subjecting it to the control of the granting state, and determining the applicable law for all legal transactions and events occurring on board.